The Pentahelix Partnership Responses during Covid-19 Pandemic in Makassar - Sukri, Sarina; Riskiyani, S.; Syafar, M. (International Journal of Statistics in Medical Research, 2023)
Background: A Partnership is one of the strategies for accelerating responses of Covid-19, especially in understanding the decisions made by the government and the various reactions of the community regarding the Covid-19 pandemic. Objective: This study aims to explore partnership efforts pentahelix involving the government, academia, community, business sectors, and the media in handling Covid-19. Methods: The qualitative study was carried out through in-depth interviews with 18 participants consisting of government, media, academics, and community elements. The participants were members of the Covid-19 Handling Task Force (Covid-19 Task Force) and people who were directly involved in handling Covid-19 in Makassar. The content analysis was performed using the collected data. The themes that emerge from the data are the pentahelix partnership with the government, community groups, academics, business sectors, and mass media. The data were collected from December 2022 to March 2023. Results: The pentahelix partnership involves 5 parties: government, community, academics, business sectors, and the media. The partnership is accomplished through coordination, collaboration, participation, and mutual assistance. This partnership is established in the implementation of government policies in handling Covid-19 with the formation of Task Forces where the community participates in its implementation. Coordination between the government and academics regarding ways to resolve the Covid-19 case; collaboration with business sectors in providing facilities and infrastructure for handling Covid-19 activities as well as with the media that assist in disseminating information, public education, and news related to the incident of Covid-19 was adopted to implement the health policies during this pandemic. Conclusion: handling covid-19 with pentahelix partnerships was carried out through coordination, collaboration, participation, and mutual assistance of all parties. The partnership process is a strategy for implementing health programs related to the handling of Covid-19 which are regulated by the government.